THE EFFECTIVENESS OF STORIGAMI IN TEACHING ENGLISH VOCABULARY: AN EXPERIMENTAL RESEARCH - MILLAH, ROIHATUL; SRIYANTO, WIDI (Linguists : Journal of Linguistics and Language Teaching, 2022)
This research aims at investigating and finding out whether storigami is effective in teaching English vocabulary for vocational higher students. Based on the researchers’ observation, most of the students have lack of vocabulary though in mastering English vocabulary is an essential thing that should be known and mastered, especially for vocational higher students who will directly face the working situation. This problem happened because, in their perspective, understanding vocabulary only can be reached through translation and memorization. The subject of this research was taken two classes purposively named control class and experimental class. The samples were taken by determining specific characteristics of students during the learning process. The experiment class applied Storigami as the treatment, while the control class applied the Grammar Translation Method (GTM). Before applying the treatment, a pre-test was conducted for both classes with the same questions. Then, after the treatment, a post-test was conducted for both classes. After collecting and analyzing the data, the researchers found that teaching vocabulary by Storigami is more effective than GTM. The finding showed that T0 :2.639 > T.Tabel: 2.01 means the null hypothesis is rejected and the experiment hypothesis is accepted, or there is any significance between X and Y variables. Furthermore, the mean score of the post-test in the experiment class is higher than the mean score in the control class. It happened because teaching vocabulary by using Storigami is more fascinating for students, and origami can be applied to building students’ English vocabulary and students’ creative thinking